2020
DOI: 10.7554/elife.62500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual inputs on neural dynamics for coding of location and running speed in medial entorhinal cortex

Abstract: Neuronal representations of spatial location and movement speed in the medial entorhinal cortex during the ‘active’ theta state of the brain are important for memory-guided navigation and rely on visual inputs. However, little is known about how visual inputs change neural dynamics as a function of running speed and time. By manipulating visual inputs in mice, we demonstrate that changes in spatial stability of grid cell firing correlate with changes in a proposed speed signal by local field potential theta fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 89 publications
(174 reference statements)
5
37
0
Order By: Relevance
“…These findings are consistent with findings of a previous study showing that glutamatergic cells in the MSDB remain tuned to running speed in the absence of optic flow (Justus et al, 2016) . The finding that visual inputs do not alter the temporal dynamics of cholinergic activity as a function of running speed are similar to findings in previous studies of a potential speed code by firing rate in neurons of the entorhinal cortex (Dannenberg et al, 2020) and posterior parietal cortex (Alexander et al, 2022) that demonstrated no change in the speed tuning of normalized firing rates. However, those studies showed a change in the gain of speed tuning of absolute firing rates.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with findings of a previous study showing that glutamatergic cells in the MSDB remain tuned to running speed in the absence of optic flow (Justus et al, 2016) . The finding that visual inputs do not alter the temporal dynamics of cholinergic activity as a function of running speed are similar to findings in previous studies of a potential speed code by firing rate in neurons of the entorhinal cortex (Dannenberg et al, 2020) and posterior parietal cortex (Alexander et al, 2022) that demonstrated no change in the speed tuning of normalized firing rates. However, those studies showed a change in the gain of speed tuning of absolute firing rates.…”
Section: Discussionsupporting
confidence: 89%
“…Theoretical work has been shown that information from optical flow could contribute to coding of location and running speed in the medial entorhinal cortex (Raudies et al, 2012(Raudies et al, , 2016. Experimental data showing the contribution of visual inputs on the spatial accuracy of grid cell firing in the medial entorhinal cortex (Chen et al, 2016;Pérez-Escobar et al, 2016;Dannenberg et al, 2020) support the idea that movement information from optical flow can contribute to speed coding in the hippocampal formation. We therefore tested the hypothesis that the relationship between the activity of cholinergic neurons in the MSDB and the animal's running speed is changed in the absence of visual information by testing the effect of darkness on the speed tuning of cholinergic activity using a linear mixed effects model of data obtained from recordings under standard lighting conditions and darkness.…”
Section: The Activity Of Cholinergic Neurons Is Linearly Correlated W...mentioning
confidence: 88%
“…The precise mechanisms of how speed and HD information are combined remain unclear, but several studies have suggested that speed cells may be more closely linked to grid cell firing than HD cells ( 189 , 193 , 209 ). Similar to grid and HD cells, the firing of speed cells is mostly context independent ( 135 ), although some changes in the speed code have been reported, for instance in darkness ( 62 , 150 , 210 ), when the shape or size of the environment is changed ( 189 ), or even when a visual pattern is changed along a linear track ( 62 ). The finding that changes in speed cell firing tend to be correlated with changes in grid cell coding suggests that speed cells may be embedded in functional grid cell modules, possibly providing part of the velocity input needed to shift activity bumps in CAN models.…”
Section: Functionally Defined Cell Typesmentioning
confidence: 99%
“…For example, horizontally displacing a visual cue in an environment reliably causes a concomitant shift in the preferred firing direction (PFD) of HD cells 21 . However, many studies have reported that HD cell responses are relatively stable in the absence of visual inputs or visual cues 14 , 26 28 . Furthermore, recordings from HD cells in young rodents just before eye-opening revealed tuned HD cells, although tuning curves were found to be broader than following eye-opening 22 , 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%